Characterization of Deep-Water Submarine Fan Reservoir Architecture: AB120 Reservoir in the Campos Basin - Zhao, Chen; Hu, Xiuquan; Li, Jianghan; Yi, Chi; Li, Jieyi; Niu, Zhipeng (Frontiers in Earth Science, 2022)
The exploration of deep-water submarine fan reservoirs has become a prominent research area for hydrocarbon discovery and recovery. However, the high operational costs render efficient exploration of this type of reservoir crucial, and the pivotal foundation lies in studying reservoir architectures. A case study of deep-water submarine fans in the Albacora Leste oilfield in Brazil is presented along with a characterization of the underground reservoir architecture based on well-log and seismic model fitting. A sedimentary microfacies distribution model is systematically established for each reservoir based on a detailed stratigraphic framework with a well-seismic joint characterization method and various types of data (e.g., geological, well-log, and seismic data). The results are as follows: the sedimentary microfacies of the deep-water submarine fans in the study area can be subdivided into tongue-shaped-lobe, muddy-channel, sandy-channel, and contourite deposits. Owing to data abundance and quality constraints, the architecture of the target layer in the study area was characterized based on Level 4 architectural elements. The AB120 Reservoir consisted of three complex channels (I, II, and III) and two tongue-shaped complex lobes (I and II). Complex channels I and III were the first and last to be deposited, respectively, and complex lobe I was deposited earlier than complex lobe II. Complex channels II and III supply complex lobes I and II, respectively. Vertically, complex lobe II was composed of three single lobes formed at different stages, the youngest of which was distributed over the largest area. Complex lobe II has already been drilled and is currently under development. However, complex lobe I has not yet been developed. This study has great practical significance for the effective development of deep-water submarine-fan reservoirs in this area and is of considerable theoretical significance for the advancement of deep-water sedimentology.